Clinical Neurology - Greenberg, David A.; Aminoff, Michael J. (Michael Jeffrey); Simon, Roger P. (New York : McGraw Hill, 2021)
"The most concise guide to one of the most complex topics in medicine updated with the latest advances in the field. Clinical Neurology, 11th Edition, provides a comprehensive overview of basic and clinical neurology in a concise, digestible format. It links clinical neuroscience to current approaches for accurately diagnosing and effectively treating neurologic disorders. Covering all the advances in molecular biology and genetics, this popular guide emphasizes history taking and neurologic examination as the cornerstones of diagnosis, and presents all information as a practice-oriented approach to neurology based on the patient's presenting symptoms or signs. This new edition covers the latest developments in neurogenetics ; pathogenesis of neurodegenerative disorders ; and treatment of neurologic infections, migraine, cluster headache, amyotrophic lateral sclerosis, spinal muscular atrophy, multiple sclerosis, epilepsy, and stroke."--taken from back cover.
Preface -- Chapter 1. Neurologic history & examination -- Chapter 2. Investigative studies -- Chapter 3. Coma -- Chapter 4. Confusional states -- Chapter 5. Dementia & memory disorders -- Chapter 6. Headache & facial pain -- Chapter 7. Neuro-ophthalmic disorders -- Chapter 8. Disorders of equilibrium -- Chapter 9. Motor disorders -- Chapter 10. Sensory disorders -- Chapter 11. Movement disorders -- Chapter 12. Seizures & syncope -- Chapter 13. Stroke -- Appendix. Clinical examination of common isolated peripheral nerve disorders -- Index.
"A Lange medical book."
Roger P. Simon's name came first on the earliest editions.
Includes bibliographical references and index.
Keywords: Nervous system -- Diseases; Neurology; Clinical medicine; Nervous System Diseases; Clinical Medicine; Neurology; Clinical medicine; Nervous system -- Diseases; Neurology